Progesterone, follicular,and estrual responses toprogesterone-based estrusand ovulation synchronizationprotocols at five stages of theestrous cycle - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2008)
The objective of this study was to monitor changes in ovarian status in heifers exposed to a progesterone insert with or without concurrent gonadotropin-releasing hormone (GnRH) injection. Estrus was manipulated in 283 heifers (31 breeding clusters) by administering GnRH, progesterone, and prostaglandin F2α(PGF2α) at 5 stages of the estrous cycle. Estrus was presynchronized with a progesterone insert for 7 days before PGF2αwas administered 24 hours before insert removal. Successive clusters of heifers were assigned to treatments (2 heifers per treatment) on cycle day 2, 5, 10, 15, and 18. Treatments consisted of a progesterone insert (day 0) for 7 days plus (1) PGF2αon day 6, 24 hours before insert removal (early PGF); (2) GnRH on day 0 + early PGF2α(GnRH + early PGF); (3) PGF2αat insert removal (late PGF); or (4) GnRH on day 0 + late PGF (GnRH + late PGF). Controls received GnRH on day 0 and PGF2αon day 7. Ovaries were scanned by transrectal ultrasonography on days 0, 2, 7, 9, and 11 to assess follicle diameters and ovulation. Blood was collected on days 0, 2, 6, 7, 8, and 9 to quantify serum concentrations of progesterone. Insemination occurred after detected estrus or by timed artificial insemination (TAI) 64 hours after insert removal. Only 25% of 141 GnRH-treated heifers ovulated by day 2; twice as many ovulated when treatment was initiated on day 5 (46.4%) than on other cycle days (20.3%). Compared with controls, progesterone concentration was greater in all progesterone-treated heifers on days 2 and 6. Early- vs. late-PGF treatment resulted in less progesterone on days 7 and 8. Pregnancy rates were less after TAI (44%) than after detected estrus (56%) and less in controls than in all progesterone treatments. Heifers in which treatments were initiated on day 10 of the cycle had the most consistent (estrus vs. TAI) pregnancy rates (65.4%) compared with heifers in which treatments were initiated on other cycle days. Compared with controls, more progesterone-treated heifers ovulated by 96 hours after insert removal. Application of the progesterone insert reduced variance of the interval to estrus after insert removal (or PGF2αinjection in controls) by 1.6-fold compared with controls. These results do not support use of GnRH in a progesterone-based synchronization protocol.; Dairy Day, 2008, Kansas State University, Manhattan, KS, 2008; Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy Day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-134-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1002; Progesterone; Follicular; Estrual; Ovulation